The image of Latin America in Rafael Gutiérrez Girardot - Gómez García, Juan Guillermo (Estudios de Filosofía, 2006)
This paper tries to establish the junctures and associations of the fundamental concepts that hold together a philosophical work, but above all, the Literary Critique of Rafael Gutiérrez Girardot. Hegel and Schlegel appear as pilars which provide a founding groundf or his critical interpretations, on which is opened the horizon of Latin America, of authors such as Jorge Luis Borges, Alfonso Reyes and César Vallejo.